TESTING SHEEP AND GOAT POX VIRUSES FOR THEIR REPRODUCTION IN PRIMARY AND SUBCULTURED CELLS - A. B. Sarbasov; B. L. Manin; R. V. Yashin; I. N. Shumilova; V. I. Diev (Ветеринария сегодня)
Results of tests of sheep and goat poxviruses for their reproduction in primary and subcultured cell cultures derived from lamb and goat kid kidneys and testicles are presented. Monolayer cultures were subcultured by 5 passages in plastic vials and infected with sheep and goat poxviruses. It was shown that production ARRIAH strain of sheep pox virus and ARRIAH 2003 strain of goat pox virus successfully propagated both in primary lamb and goat kid kidney and testicle cell cultures and lamb and goat kid kidney and testicle cell subcultures. Activity of sheep and goat poxviruses passaged 5 times was 5.5–6.0 lg TCID50/cm3. Taking into account that modern cell cultivation conditions allow primary trypsinized cell populations subcultivation up to 25–30th passage, subcultures together with continuous cell lines can be used for large-scale sheep and goat poxvirus production and research purposes.